Peran Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Kinerja Guru: Studi Kasus di Sekolah Dasar - Ivon Mukaddamah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to The Role of Principal Transformational Leadership in Improving Teacher Performance: Case Study in Elementary Schools. This type of research is a literature study. Data collection with documentation. Data analysis with SLR. The principal's transformational leadership plays an important role in improving teacher performance in elementary schools. By inspiring and motivating teachers through a clear vision, emotional support, and providing freedom to innovate, school principals are able to create a work environment that is conducive to teacher professional development. In addition, leadership that emphasizes collaboration and recognition of teacher achievements has proven effective in encouraging their work enthusiasm and commitment to improving the quality of education. Through this approach, school principals can significantly improve teacher performance, which ultimately has a positive impact on the quality of learning in elementary schools